Prognostic value of lymphocyte subsets in diffuse large B cell lymphoma - Qiu, Lihua; Xing, Lijing; Zhao, Meng; Sun, Biwen; Zhou, Xinpei; Li, Min; Ying, Guoguang; Zhang, Huilai; Tian, Chen (Frontiers in Oncology, 2025)
IntroductionAlthough some clinical prognostic parameters and gene expression features have been identified to be associated with the prognosis of diffuse large B cell lymphoma (DLBCL), clinical outcomes of DLBCL remains unpredictable. Lymphocyte subpopulations are considered to be prognostic factors for DLBCL, however due to the small sample size, conflicting views exist.Methods301 newly diagnosed DLBCL patients treated at our center from January 2015 to December 2019 were retrospectively analyzed to explore the relationship of lymphocyte subsets and prognosis prediction.ResultsIn this retrospective single-center study, patients with more severe disease, defined by either advanced Ann Arbor stage or a high-risk IPI score, consistently exhibited significantly lower percentages of CD19+ B cells, CD4+ T cells and CD4+/CD8+ ratio, while percentage of CD8+ T cells were significantly higher. There were no significant differences in percentages of CD3+ T cells and CD16+CD56+ NK cells. Correlation analysis revealed significant associations between lymphocyte subsets and clinical features such as Ann Arbor stage, IPI score, lactate dehydrogenase (LDH), beta-2 microglobulin (b2-MG), Ki-67, age, and neutrophils. Higher percentages of CD19+ B cells, CD4+ T cells, and CD16+CD56+ NK cells, a higher CD4+/CD8+ ratio, and a lower percentage of CD8+ T cells at diagnosis predicted good response after R-CHOP treatment. Multivariate analysis indicated that a low CD4+/CD8+ ratio was independently associated with worse PFS (p=0.049) and showed a trend toward worse OS (p=0.086). Patients were dichotomized into high and low groups using the median value of CD4+/CD8+ ratio, Kaplan-Meier analysis showed that patients with CD4+/CD8+ ratio ≥1.19 had significantly longer PFS and OS compared to those with CD4+/CD8+ ratio <1.19.DiscussionLymphocyte subsets, especially CD4+/CD8+ ratio, could be recommended as a potential prognostic indicator for DLBCL.